Diseño conceptual de una planta para el aprovechamiento de caucho molido de neumáticos usados a partir de pirólisis (2018)
The present work of degree realizes the conceptual design of a pyrolysis plant for the production of Carbon black and Fuel Oil, employing as raw material granule of rubber recycled (GRC) produced by companies crushers of tires used or out of use (NFUs) , in the urban perimeter of the city of Bogotá D.C. Initially the national market of the products of interest is identified, to establish a market segment for the Carbon black and Fuel Oil that can be satisfied based on an analysis of Supply of the raw material or GRC for Bogotá D.C .; In addition, based on the production yields obtained experimentally, the processing capacity of the plant of 120 tons GRC / month is established, together with a production capacity of 63 tons of Carbon Black / month and 29 tons of Fuel Oil / month.